A multi-family cluster of COVID-19 associated with asymptomatic and pre-symptomatic transmission in Jixi City, Heilongjiang, China, 2020 - Hongyang Zhang; Chengcheng Hong; Qulu Zheng; Pengzheng Zhou; Yuliang Zhu; Zhongkai Zhang; Qifang Bi; Ting Ma (Emerging Microbes and Infections, 2020)
ABSTRACTWe investigated a multi-family cluster of 22 cases in Jixi, where pre-symptomatic and asymptomatic transmission resulted in at least 41% of household infections of SARS-CoV-2. Our study illustrates the challenge of controlling COVID-19 due to the presence of asymptomatic and pre-symptomatic transmission even when extensive testing and contact tracing are conducted.